The Influence of the Concept of Leisure on Sustainable Tourism - Sadowski, Ryszard F. (Studia Ecologiae et Bioethicae, 2018)
The article presents: 1) the evolution of the concept of leisure; 2) the challenges facing contemporary civilization in terms of leisure; and 3) the concept of leisure, which promotes sustainable tourism. According to the author only concept of leisure, which takes into account all the potentiality of human being – with his biological, emotional, spiritual and cultural needs – guarantees effective practice of sustainable tourism. Upbringing and education play an important role in reaching such a concept of leisure.